Discoloration problem after partial pulpotomy with wMTA: case report - Alev Alaçam; Didem Sakaryalı; Gülçin Akca (Gazi University, 2016)
Introduction: This case report conveys the prognosis of partial pulpotomy treatment of complicated crown fractures in maxillary permanent incisors using white Mineral Trioxide Aggregate (wMTA) or calcium hydroxide in a 9 year-old boy. Case report: The patient was referred to the clinic with complicated crown fractures in both maxillary central incisors due to trauma. Partial pulpotomy was done in both teeth. Calcium hydroxide was selected as a conventional pulp capping agent for tooth number 11 and wMTA was selected for tooth number 21. Unfortunately, 3 months later, the patient had a secondary trauma to tooth number 11 necessitating endodontic treatment, fiber-post and strip-crown restoration. Six months later, discoloration was observed in tooth number 21. The colored material including wMTA and the dentin was removed under operating microscope and the restoration was renewed. Microbiological evaluation of the removed material showed negative culture for aerobic and anaerobic bacteria, and fungus. The tooth number 21 remained vital and a dentin bridge was confirmed clinically and radiographically at 12 and 24 months follow-up visits and there was no further esthetic problem. Conclusion: As a result, it can be concluded that the use of wMTA for partial pulpotomy needs to be reconsidered for esthetical reasons.